Caught in the Belly of a Paradox: A Response to Ronald M. Green's Review of the "Journal of Religious Ethics" - Swearer, Donald K. (Journal of religious ethics, 1997)
Careful examination of the facts of record shows that the JRE has been as successful as its competitors in expanding the cultural range and scope of inquiry in religious ethics. Yet it should be noted that the debate between cultural particularists and philosophical ethicists, a debate that has shaped the actual practices of the field of comparative religious studies, has not been vigorously pursued in these pages. Likewise, the JRE has not yet realized its potential to foster collaborative work among scholars working in different religious traditions, to encourage attention to neglected topics, or to enlarge, through fuller attention to diverse religious traditions, the range of ethical and metaethical interests that dominate inquiry in religious ethics.